The respective parts of incidence and lethality in socioeconomic differences in cancer mortality. An analysis of the French network Cancer registries (FRANCIM) data - Joséphine Bryere; Laure Tron; Gwenn Menvielle; Guy Launoy; the French Network of Cancer Registries (FRANCIM) (BMC, 2019)
Abstract Background To determine relevant public health actions and to guide intervention priorities, it is of great importance to assess the relative contribution of incidence and lethality to social inequalities in cancer mortality. Methods The study population comprised 185,518 cases of cancer diagnosed between 2006 and 2009 recorded in the French registries. Survival was known for each patient (endpoint: 30/06/2013). Deprivation was assessed using the European Deprivation Index. We studied the influence of deprivation on mortality, incidence and lethality rates and quantified the respective proportions of incidence and lethality in social inequalities in mortality by calculating attributable deaths. Results For cancers with social inequalities both in incidence and lethality, excess mortality in deprived was mainly caused by social inequalities in incidence (e.g. men lung cancer: 87% of excess deaths in the deprived caused by inequalities in incidence). Proportions were more balanced for some cancer sites (e.g. cervical cancer: 56% incidence, 44% lethality). For cancer sites with a higher incidence in the least deprived (e.g. breast cancer), the excess-lethality in deprived leads entirely the higher mortality among the deprived. Conclusions Most of the excess mortality in deprived is due to the excess incidence of tobacco-dependent cancers and the excess lethality of screenable cancers.